On the existence of interpolating SK-splines - Serdyuk, A. S.; Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We establish new sufficient conditions for the existence and uniqueness of generalized interpolatingSK-splines with uniformly distributed interpolation nodes. Our results include all known important assertions obtained in this field as special cases.